P161 Unmet needs in the treatment of idiopathic pulmonary fibrosis (IPF) – insights from patient chart review in five european countries. (15th November 2016) - Maher, TM; Molina-Molina, M; Russell, A-M; Bonella, F; Jouneau, S; Ripamonti, E; Axmann, J; Vancheri, C
Abstract : Introduction and objectives: Two antifibrotic drugs, pirfenidone and nintedanib, are approved by the FDA and EMA for the treatment of IPF. We investigated treatment patterns of European patients with IPF to understand antifibrotic treatment uptake and identify unmet needs in IPF treatment practice. Methods: Between February and March 2016, respiratory physicians from France, Germany, Italy, Spain and the UK participated in an online questionnaire designed to collect information on IPF treatment patterns. Responses were collected from physicians who had consulted with ≥6 (France, Italy, Spain) or ≥10 (Germany, UK) patients with IPF (within 3 months). Patients were categorised as being in the treated population (those who had received approved antifibrotics) or the untreated population (those who had not received approved antifibrotics, but may have received other therapies). Classification of IPF diagnosis (confirmed/suspected) and severity (mild/moderate/severe) for each patient was based on the individual physician's report. Results: Overall, there were 290 respondent physicians reporting on 1838 patients. Of 1783 patients with data, 54% were not treated with an approved antifibrotic. Of patients with a confirmed IPF diagnosis, 41% were not treated. In the 1737 patients analysed, the untreated population was older than the treated population (70 versus 67 years, respectively; p ≤ 0.01) and had less frequent multidisciplinary team (MDT) evaluation (57% versus 83%, respectively; p ≤ 0.01). At diagnosis, mild, moderate and severe IPF was reported in 43%, 40% and 16% of untreated patients, and 26%, 64% and 10% of treated patients, respectively. Average forced vital capacity (FVC) at diagnosis and last check-up was significantly higher in untreated patients versus treated patients (both p ≤ 0.01; Table); however, fewer untreated patients had an FVC measurement at their most recent check-up compared with treated patients (12% versus 26%, respectively; p ≤ 0.01). Conclusions: Despite recent regulatory approval of antifibrotic therapies, many European patients with confirmed IPF do not receive approved antifibrotic treatment. Possible explanations may include: lack of MDT diagnosis; lack of referral to specialist centres; patients not meeting treatment thresholds; subjective perceptions of disease severity; reluctance to treat patients with 'stable' disease; variations in patient/physician awareness or knowledge of IPF; or lack of confidence in prescribing new treatments.